Diskon Vonis Mati: Tinjauan Hukum Pidana Islam terhadap Putusan Mahkamah Agung tentang Kasus Ferdy Sambo (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2023)
The Supreme Court of the Republic of Indonesia, in its ruling, declared the rejection of the cassation filed by Ferdy Sambo concerning the premeditated murder case against him. However, simultaneously, the cassation decision corrected the death penalty imposed by the South Jakarta District Court to a life imprisonment sentence. This research aims to elucidate the considerations of the Supreme Court judges from the perspectives of positive law and Islamic law. The study employs a normative-empirical juridical approach and analyzes Islamic criminal law aspects. Data sources include the rulings of the South Jakarta District Court, the Jakarta High Court, and the Supreme Court. The findings indicate that some aspects of the Supreme Court cassation ruling are relevant to Islamic criminal law, while others are not. Aspects relevant prioritize considerations of prevention, rehabilitation, and eliciting remorse from the defendant. On the other hand, considerations related to the defendant's services and social history towards the state are irrelevant to Islamic law, as these aspects are not part of a criminal act.